Hemangioma and port-wine stain. Are they really distinct entities? - Bonifazi, E.; De Roma, M.R.; Conca, R. (European Journal of Pediatric Dermatology, 2001)
Hemangioma and port-wine stain are two distinct entities from the clinical and evolutive point of view. However, they possibly share a common pathogenesis, as supported by reference to other disorders, the higher frequency of both conditions in premature babies and, finally, the clinical course of the precursors of hemangioma and of metameric hemangioma.